Cytogenetic Analysis of Five Crotalaria Species (Papilionaceae) - Cequea Ruíz, Hernán; Díaz de Cequea, Damelis; Imery, José (Boletín del Centro de Investigaciones Biológicas, 1970)
Root tips and flower buds from plants of five Crotalaria species collected in Sucre and Monagas States, Venezuela, were squashed and stained in FLP orcein to analyze mitotic and meiotic chromosomes. Crotalaria incana (2n = 14), C. retusa (2n = 16), C. purdiana (2n = 16), C. vittelina (2n = 16), and C. anagyroides (2n = 16) exhibited small (1.7”“4.5 Î¼m), median point (M), median region (m) and submedian region (sm) chromosomes. Mean number of chiasmata per cell, in diplotene, diakinesis and metaphase I, ranged from 15.10 to 9.92. Dicentric bridges and acentric fragments in pollen mother cells, at anaphase I, showed that C. purdiana plants are heterozygous for a paracentric inversion, and may produce aneuploid organisms by non disjunction of a pair of homologous chromosomes. The 84.2% fertility in C. purdiana showed that a simple or double crossing over took place within reverse inversion loops between inverted and normal chromosome segments at pachytene, reducing fertility by producing genetically abnormal gametes. These species fit the genetic system, where bivalents have normal chromosome pairing at pachytene and a nonrandom chiasmata distribution, with one and two chiasmata in diplotene, diakinesis and metaphase I, and are essentially equal in crossover frequency.